The Nature of Diamino Linker and Halogen Bonding Define Selectivity of Pyrrolopyrimidine-Based LIMK1 Inhibitors - Ariawan, Daryl; Au, Carol; Paric, Esmeralda; Fath, Thomas; Ke, Yazi D.; Kassiou, Michael; van Eersel, Janet; Ittner, Lars M. (Frontiers in Chemistry, 2021)
The LIM-domain kinase (LIMK) family consist of two isoforms, LIMK1 and LIMK2 which are highly homologous, making selective inhibitor development challenging. LIMK regulate dynamics of the actin cytoskeleton, thereby impacting many cellular functions including cell morphology and motility. Here, we designed and synthesised analogues of a known pyrrolopyrimidine LIMK inhibitor with moderate selectivity for LIMK1 over LIMK2 to gain insights into which features contribute to both activity and selectivity. We incorporated different stereochemistry around a cyclohexyl central moiety to achieve better selectivity for different LIMK isoforms. Inhibitory activity was assessed by kinase assays and biological effects in cells was determined using an in vitro wound closure assay. Interestingly, a slight change in stereochemistry alters LIMK isoform selectivity. Finally, a docking study was performed to predict how the new compounds interact with the target.